79-3x=2x-9

Simple and best practice solution for 79-3x=2x-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 79-3x=2x-9 equation:


Simplifying
79 + -3x = 2x + -9

Reorder the terms:
79 + -3x = -9 + 2x

Solving
79 + -3x = -9 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
79 + -3x + -2x = -9 + 2x + -2x

Combine like terms: -3x + -2x = -5x
79 + -5x = -9 + 2x + -2x

Combine like terms: 2x + -2x = 0
79 + -5x = -9 + 0
79 + -5x = -9

Add '-79' to each side of the equation.
79 + -79 + -5x = -9 + -79

Combine like terms: 79 + -79 = 0
0 + -5x = -9 + -79
-5x = -9 + -79

Combine like terms: -9 + -79 = -88
-5x = -88

Divide each side by '-5'.
x = 17.6

Simplifying
x = 17.6

See similar equations:

| 12x-2=7x | | 4x^2+ab-2ax-2bx=0 | | y=5x^2-30x+20 | | (X+2)(x-4)=16 | | (4w+8)/(w^2-4w)(w^2-3w-4)/(w^2-3w+2)=0 | | 20a^3-39a^2+18a=0 | | 59-4x=10x-17 | | 6d+1=4d+7 | | 9(a+9)=104.4 | | 6x(x-5)=0 | | (5x-8)(4x-9)= | | 3x+59=8x-6 | | h=32+-16t^2 | | 2(3)-5(-4)=-10 | | 18(2m+11)= | | 13.4=3c-7 | | 4e-6=12 | | 11x+7y=180 | | 20v^2+19V+3=0 | | 2p=16.6 | | -x/5=-14 | | (-4X^2+X+5)+(4-3X-X^2)=0 | | (2x+7)(5x+2)= | | 8(a+3)=40 | | x^2-34x+323=0 | | (5-X^2-2X^4)-(-6X^2+5X+5)=0 | | 74-4x=5x+24 | | x^2-36x+324+x^2-2x-1=x^2 | | 6x-4=3x-60 | | 9x-135=4x-5 | | 3x+37=10x+-26 | | 3.14r=7.51 |

Equations solver categories